Impact of Outcome Based Education (OBE) on Teaching Effectiveness of Faculty Members of Professional Program - Vaishali Rahate1 , Sujit Metre2 , Ranjit Ambad3 , Swapnil Bhirange4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The growth and development of a country relies heavily on the Higher education which powers the supplyof skilled and technologically advanced manpower.Outcome based education is potentially successful curricular innovation for educational institutions asit not only overcomes the lacuna of traditional learning process but also it has the advantage of beingfuture driven. OBE aims at assessing the learners on understanding, critical thinking, reasoning, reflectionand action. It aims at ensuring that the students have an integration of knowledge and learning relevantand connected to real-life situations. Looking at the growing importance of Outcome based Education(OBE), This study is conducted to find the OBE literacy quotient of the faculty members in Management& Engineering colleges. A preview is generated with respect to the acceptance and/or reluctance of facultymembers towards implementing OBE practices. The study also postulates the relationship between OBEknowledge and teaching effectiveness.The data is analyzed through descriptive and inferential statistics.The outcome of the research would be significant for the policy makers and administrators in determiningthe means to improve quality of education by proper implementation of OBE practices.